Design and optimization of powertrain system for automated controlling system on prototype fuel cell electric vehicle - Omar, S.M.H.S.; Arshad, N.M.; Yassin, I.M.; Fakharuzi, M.H.A.M.; Ward, T.A. (2014)
This paper reports analysis on an automatic intelligent controller use to drive a prototype fuel cell electric vehicle while maintaining maximum efficiency and completing a course with in a specific period of time. The objective is to reduce driving error while minimizing energy usage for the Shell Eco-marathon Asia 2014 race. The vehicle is equipped with a proton exchange membrane (PEM) fuel cell system, brush DC motor and DC/DC converter. This prototype vehicle is a single seater with streamline body shape that is designed for energy-efficiency race with the objective of driving the archive furthest distance with the least amount of fuel within the specific time given. In the design’s process, the car’s fuel cell efficiency test, energy demand, track behavior, motor efficiency analysis, and driving control strategy must be conducted. Experiment on automated intelligent controller was conduct to analyze the performance of powertrain system for certain time given. This powertrain system for automated intelligent controller analysis is part of energy efficiency study for electric vehicle. It forms the basis of knowledge for the energy efficiency analysis.